Autismo infantil na teoria do amadurecimento de Donald Winnicott e suas repercussões clínicas - Silva, Filiciana Ferreira (2023)
This work consists of presenting Winnicott's theory of maturation, discussing the stages of primitive emotional development related to the central axis of the research, which is “autism in Winnicott's theory of maturation”. This research seeks to find one of the factors that may be related to the etiology of autism, which is the need for an environment good enough and adapted to the needs of the baby. Autism is studied by Winnicott from the field of psychoses and recognizes characteristics of childhood schizophrenia in it, that being a successful defense against an environment that was not a facilitator for the maturation process. Autism is, then, a defense provoked by the split that occurs in the baby in a primitive phase of emotional development, where the symbolic register is not yet present and the infant, then, reaches an invulnerability and remains unreachable and untouchable by the environment. The first sign of autism in children is the lack of eye contact, a behavior resulting from the lack of experience in a mutual relationship between mother and baby. The analyst's intervention in the invulnerability situation should occur as close as possible to the period of the environmental failure, for this reason, early intervention is so effective. The intervention process should occur through organized clinical regression. Throughout this work, the main concepts of Winnicott's theory of maturation will be resumed and will be correlated with the specificities of autism